Efeitos do AMPc intracelular sobre a diferenciação de células progenitoras neurais - Schmiddel, Felipe (2022)
Intermediate and extrinsic intrinsic stimuli contribute to the growth of progenitor cells (NPCs). Extracellular stimuli cause NPCs to differentiate into glial cells and neurons. At the intracellular level, as signaling pathways, cyclic adenosine (cAMP) expression is also dependent on the control of gene expression, such as cell transition processes and neurite outgrowth. The production of cAMP is directly related to the increase in deneurite growth in different cell lines, but the effects of this second line of growth on NPCs are not yet fully understood. To investigate the effects of cAMP on an augmented model of NPCs, which are augmented of the model of NPCs, which increase the capacity of NPCs, which encompass the neurospheres of most neural processes that extend into the early stages of development. This is, therefore, an excellent in vitro study model to assess the influence of cAMP-dependent pathways on these processes. Therefore, in this study, we investigated the effect of cAMP in the study of cAMPs that contemplate an increase in the development of neurogenesis, neurogenesis, gliogenesis and migrations in NPCs in vitro. We observed that the cAMP of the NPCs is potentiated, dibutyryl cAMP (db-cAMP) and pertussis toxin (PTX). The db-cAMP increased the measurement, of the NPCs, in which it increased the frequency of neuronal positive for beta-3-tublin and MAP2+, neurite outgrowth cells. Neural migratory PTX was further configured in treated NPCs or with a reduced number of cells that have distanced themselves from neuroscience. It is concluded that cAMP signaling pathways stimulate neuron growth and stimulate NPC migrations during cell media.